Preliminary experience with the Pipeline Flex Embolization Device: technical note. (27th August 2014) - Martínez-Galdámez, M; Gil, A; Caniego, J L; Gonzalez, E; Bárcena, E; Perez, S; Garcia-Bermejo, P; Ortega-Gutierrez, S
Abstract : Background: Clinical experience with the Pipeline Embolization Device (PED) has been widely described in the literature since it obtained its European CE and FDA approvals in 2008 and 2011, respectively. The new generation of PED, the Pipeline Flex Embolization Device, received the CE mark of approval in March 2014. While the implant composition has not changed, its new delivery system has some differences. One of the main changes from the previous generation is a new delivery system that makes the device resheathable until deployed over 90% of its length. We present our preliminary experience using this device. Methods: Between May and June 2014, six patients with six aneurysms were treated with the Pipeline Flex device. Results: All devices were placed properly, without technical difficulties. We successfully resheathed and repositioned the device in two cases. Minor and major intraprocedural or periprocedural events were noted. Conclusions: The Pipeline Flex device allows more precise and controlled deployment than the current PED device. Although this preliminary experience seems positive, multicenter larger series will be needed to confirm the safety and durability of this new device.